Nivolumab Induced Seronegative Arthritis in a Patient With Refractory Hodgkin’s Lymphoma - Seda ÇOLAK,; Ahmet OMMA, (Archives of Rheumatology, 2019)
Nivolumab is a monoclonal antibody against programmed cell death protein-1 which is assessed in the group of immune checkpoint inhibitors. It may lead to immune-related adverse events. In this article, we report a 38-year-old male patient diagnosed with seronegative arthritis after nivolumab therapy. This case supports that clinicians should be attentive for immune-related adverse events after use of immune checkpoint inhibitors.